Interactive PowerPoint Learning Media on Beginning Reading Skills of Grade 2 Elementary School Students: Media Pembelajaran PowerPoint Interaktif Terhadap Keterampilan Membaca Permulaan Peserta Didik Kelas 2 Sekolah Dasar - Cahyani, Dia Mutia Nur; Liansari, Vevy (Universitas Muhammadiyah Sidoarjo, 2023)
This study was conducted to determine the presence or absence of the influence of interactive PowerPoint Learning media on the initial reading skills of Grade II SDN Candiharjo students. This study uses quantitative experimental research method with Pre Experimental Design research with Nonprobability Sampling technique that is saturated sampling in taking subjects, one group Pretest-Posttest design. This study used 33 subject of Class II learners. The results of hypothesis testing using Paired Sample T-Test. In the Pretest-Posttest hypothesis test obtained the value of Sig (1-tailed) 0,000 < 0,05 and thit 16,543 > ttab 2,040, so it can be concluded that there is a large positive and significant influence between the use of interactive PowerPoint Learning media on the initial reading skills of Grade II Elementary School Students.